Assessing the role of social enterprises in shaping eco-social agriculture: Evidence from smallholder organic growers in West Bengal (India) - Arindam Laha; Nilojyoti Koner; Santanu Kumar Ghosh (United Nations Research Institute for Social Development (UNRISD), 2024)
The potential of Social and Solidarity Economy (SSE) in the agricultural sector lies in designing people-centric and planet-sensitive approaches that recognize the multifunctional nature of agriculture in producing not only commodities, but also non-commodity outputs such as environmental services, landscape amenities and cultural heritage, and social services. Applying SSE approaches in agriculture is considered a response to intensive farming, which deviates significantly from the traditional nature-based social contract. In this context, an intervention of social enterprises in shaping eco-social agriculture can enable smallholders to restore their earlier contracts with nature. This study contributes to the existing literature by addressing a lack of empirical research on social farming experiences in the global South and the role of social enterprises in facilitating eco-social agricultural initiatives. This study presents empirical research on the role of ONganic Foods-a social enterprise that has developed a strong relationship with smallholder organic producer groups in the Nadia district of West Bengal-in supporting ecosocial agriculture. A progressive alliance between the local organic smallholder group, ONganic and the state supported the integration of local smallholders in eco-social transformation processes. The evidence presented in the paper shows that eco-social agriculture can contribute to fulfilling the Sustainable Development Goals (SDGs) at the local level.
Keywords: 330